Consumers’ perceptions of online retailers’ brand innovativeness on customer brand identification and loyalty - Siti Nor Bayaah Ahmad; Haslinda Hasan; Irma Wani Othman; Salmah Topimin (Academic Inspired Network, 2021)
The current study examines consumers’ perceptions of the local gold and jewelry retailers in Malaysia in terms of business innovation through co-creation and service innovation, as well as the impact on consumer-brand identification and brand loyalty. This study intends to inspect the consumer perceptions of innovativeness and consumer brand identification models, with a particular emphasis on how consumers perceive business innovativeness in terms of co-creation and service innovation. Customers’ perceptions of brand innovativeness are assessed in this study using their brand identification and loyalty. Will any business effort in innovativeness be identified and aligned with the customers’, and will this make the customers more loyal to a brand name? Based on the findings, significant associations were discovered between customers’ co-creation and brand innovativeness, between service innovation and brand innovativeness, between brand innovativeness and consumer-brand identification (CBI), and between CBI and brand loyalty. Because the primary objective of this study is to ascertain the effect of consumers’ perceptions of business innovation on brand identification and loyalty, the focus will be narrowly focused on this subject. Due to the rapid pace of change and the availability of new products, the factors that contribute to customer loyalty may no longer be as well understood. This study establishes the framework by incorporating pertinent literature and delves deeply into brand identification, brand loyalty, and brand innovation. The primary objective is to engage in and expand an investigation into understudied Malaysian gold and jewelry traders who communicate with their customers via social media. By viewing brand innovation as an extrinsic information cue, marketers can gain a better understanding of their customers and respond appropriately to their needs.